Simile in the poetry of Ahmed Nalband Volume three as an example - Nawzad Abdullah Haji (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research is an attempt to apply a gender simile to that of Ahmed Nalband, and this rhetorical element is one of the most famous rhetorical elements in the text of poetry. This research is entitled (Simile in the poetry of Ahmed Nalband Volume 3 as an example). it consists of two main sections. the first section highlighted simile in terms of definition and types. The second section is practical. And this is specialized to the emergence of four types of simile in Nalband's poetry. The eloquent simile and meditation came in the first place and humanity and the simile of the reverse and the savior in the third and fourth place of eloquence learn literary since the advanced appeared its existence in literary texts. And similar the rhetorical races are recreated side by side and used for extended quality in literary texts